Overview of meningococcal epidemiology and national immunization programs in children and adolescents in 8 Western European countries - Pinto Cardoso, Gaëlle; Lagrée-Chastan, Marion; Caseris, Marion; Gaudelus, Joël; Haas, Hervé; Leroy, Jean-Philippe; Bakhache, Pierre; Pujol, Jean-François; Werner, Andreas; Dommergues, Marie-Aliette; Pauquet, Emilie; Pinquier, Didier (Frontiers in Pediatrics, 2022)
Background: In Europe, meningococcal (Men) vaccines are available against 5 of the 6 serogroups (Men) responsible of nearly all cases of invasive meningococcal disease (IMD). Meningococcal vaccination has been introduced in the national immunization programs (NIPs) for children and adolescents of numerous European countries, but with no consistent strategy across countries. Objectives: To describe IMD epidemiology, NIPs, and vaccination coverage rates (VCRs) in children and adolescents in 8 Western European countries. Methods: Epidemiological data (from 1999 to 2019), NIPs regarding meningococcal vaccination status, and VCRs were collected from the European Centre for Disease Prevention and Control (ECDC) and/or national websites. Results: MenB was the most common serogroup. In Belgium, Spain, France, the Netherlands, the United Kingdom (UK), and Portugal, incidence was greater for MenW than MenC. In 2019, MenB risk was covered in 2 countries (Italy, UK). MenC risk was covered in all countries, via MenC (countries: N=4), MenACWY (N=2), or MenC (infants/children) and MenACWY (adolescents) (N=3) vaccination. VCRs were higher in children than adolescents. Conclusion: Our study confirmed the diversity of NIPs, including in neighboring European countries with similar factors like economic resources and epidemiological risk, thus indicating that other factors underlie NIPs. Convergence toward a more common immunization program including MenACWY and MenB vaccination would promote equity and safe travel regarding infectious diseases for young people, and possibly improve the understanding of vaccination by patients and healthcare professionals.